Структура і властивості литих сталей у зв’язку з термокінетичними параметрами обробки і кристалізації розплаву - Kondratyuk, S.Ye.; Veis, V.I.; Parkhomchuk, Z.V.; Tokareva, O.O. (Physico- Technological Institute of Metals and Alloys of the NAS of Ukraine, 2019)
The effect of the overheating temperature of steel melts above equilibrium liquidus (20…170 °C) and cooling rate at crystallization (5…650 °C/c) on characteristics of cast structure and mechanical properties of  structural steels 25Л, 25ХГСТФЛ, 45Л, 45ХГСТФЛ was researched. The regular increase in the dispersion and mechanical properties of their cast structure under conditions of rapid cooling and an increase in the temperature gradient during crystallization was established. Based on the results of experiments, interpolation equations of the effect of melt overheating and cooling rates on the structural and mechanical properties of steels are obtained. The obtained equations allow to predict the properties of castings within the studied factor space.